Anesthesia and Hematological and Electrocardiographic Changes in the Emergency Care of a Hooded Capuchin (Sapajus cay) - da Silva, Angela Maria; dos Santos, Dayane Mendes; Flores, Carla Pinheiro da Luz; Machado, Marielza Pansera; Tomé Melo, Andréia Lima (Acta Scientiae Veterinariae, 2021)
Background: The hooded capuchin that occurs in the Brazilian states of Mato Grosso and Mato Grosso do Sul belongs to the species Sapajus cay. This robust species of capuchin monkey is characterized by its highly varied diet. Although it is well adapted to the natural environment, the survival of this species has come under increasing threat. In fact, several animals have been rescued and taken into veterinary medical care, where its correct capture and restraint minimize the occurrence of adverse effects to the animal and to veterinary anesthesiologists. This paper reports on the emergency care of a hooded capuchin (S. cay) rescued by the Environmental Police of the state of Mato Grosso do Sul, Brazil, and sent to veterinary medical care. Case: An adult female hooded capuchin, weighing 1.6 kg, was subjected to veterinary care to treat trauma probably caused by being run over. The animal exhibited intense prostration, 10% dehydration, pale and slightly jaundiced oral and ocular mucous membranes, impaired consciousness, cachexia, muscle weakness, sarcopenia, a probable fracture in the proximal portion of the left tibia and a laceration and possible fracture of the right metatarsus. The patient was stabilized by subjecting her to fluid therapy with Ringer’s lactate solution supplemented with glucose and vitamins. The animal was anesthetized with an intramuscular injection of 11 mg/kg ketamine and 0.6 mg/kg midazolam, and blood count, serum biochemistry and electrocardiography were performed. Blood tests revealed hypochromic microcytic anemia, liver disease and a slight increase in urea to 56 mg/dL (reference: 14.4-48.9 mg/dL). The electrocardiogram revealed the following: HR: 260 b.p.m; P axis: -115.36º; QRS axis: 50.17º; T duration: 36 ms; R amplitude: 0.68 mV; P amplitude: 0.17 mV; P duration: 44 ms: PR interval: 52 ms; S amplitude: -0.12 mV; T amplitude: 16 ms; ST elevation: -0.05 mV; QT interval: 106 ms; Q amplitude: -0.2 mV; QRS duration: 54 ms. The patient exhibited tachycardia and sinus rhythm. Antibiotic treatment was administered via intravenous (IV) injection with 50 mg/kg ceftriaxone and 25 mg/kg metronidazole, while analgesia was administered subcutaneously (SC) with 2 mg/kg tramadol hydrochloride and 25 mg/kg sodium dipyrone and intramuscularly (IM) with 0.2 mg/kg meloxicam. The patient was stabilized and transferred by the Environmental Police to the Wild Animal Rehabilitation Center (CRAS) located in the municipality of Campo Grande, Mato Grosso do Sul, to continue its treatment, perform complementary tests such as radiography of the fractured limb and clinical and surgical treatment. Discussion: Proper physical restraint is essential to the success and quality of biological samples that are collected. Surgical procedures, simple clinical exams and the collection of biological material may all require the use of anesthetics, and the type most commonly used for the restraint of wild animals are dissociative anesthetics. Ketamine is an neuroleptanalgesic drug widely used in primates, and can be administered separately or in combination with other anesthetics, such as midazolam, to increase chemical restraint and anesthesia and enable handling of the patient. As for hematological changes, female nonhuman primates are known to undergo blood loss during their menstrual cycle, which reduces the parameters of the erythrogram. In the case of this capuchin, the blood count revealed hypochromic microcytic anemia, which may be related to the menstrual cycle of the species. With regard to biochemistry serum levels, liver function showed the greatest change, with altered aspartate aminotransferase - AST (368 U/L) and alanine aminotransferase - ALT enzyme levels (151 U/L), indicating possibly chronic liver damage. On the other hand, research involving Cebus flavius found that adult males had higher ALT levels than juveniles.